Saúde mental na atenção básica : atuação das equipes da estratégia saúde da família - Pini, Jéssica dos Santos (2009)
After the psychiatric and primary care reformulation, the mental patient (MP) returns to his family and community, requiring the assistance of the Family Health Strategy (FHS). It is known that these teams are still organizing themselves to provide care for these individuals, since it is a recent responsibility. Thus, this study aimed at evaluating the actions carried out by the FHS towards the MP and their families, and understanding the strengths and difficulties these professionals face to give a mental health care. An exploratory, descriptive qualitative analysis was employed, using the focal group strategy to gather data in the city of Maringá - PR. First, two Basic Health Units (BHU) were chosen. These two BHUs forwarded most individuals to the psychiatric emergency of Maringá Municipal Hospital and had more subjects enrolled in the Integrated Center for Mental Health in its area. A focus group with FHS staff was assembled in each BHUs. This group had professionals from all occupational categories and in sufficient numbers to cover their service area. Bardin's content analysis was used to analyze the data. The Ethics and Research Committee and the Municipal Health Department of Maringa granted their permission to carry out the study. The participants signed a consent form and agreed to the recording the focus group. Activities carried out during the MP's monitoring and crisis were identified in the discussions. the monitoring activities consisted of home visits, creation and strengthening of bonds, the MP's social reinsertion, medication, referral to services and professional expertise, guidance to the MP and his/her family and assistance to family members. The following actions were taken on a breakdown: episode assessment, referral to emergency psychiatric, team's commitment and the search for psychiatric hospitalization. As for factors affecting the care of MPs there were more problems than facilities; negative feelings, lack of professional training, prioritization of remedial activities, the existence of criteria for treatment/monitoring, or the lack thereof, inadequate reference and counter reference, the CAPS team activities in the logical matrix, the bonds among the MP/family/team, lack of accountability, participation, support and knowledge of the family, FHS refusal to perform, and poor adherence to the indicated therapy by the MP. It was noticed that the teams are carrying out several actions towards the MPs, keeping in mind the deinstitutionalization principles and perceiving themselves as the main caregivers for those in their service area. However, in order to assist the MP, these professionals are repeatedly faced with factors that affect their actions and, upon reflecting, they saw they had the power to change them through discussion with the other BHUs team members, the mental health network service, managers and community. At the end of the study, a considerable progress was noted on the part of the FHS in assisting the MP at all times they are within the community. It was also noted that this is a transition time where the professionals need to carry out activities and participate in a network that is still under construction, besides reformulating their way of thinking mental health, their beliefs regarding the MP and the care that should be offered them. Thus, it is the team's duty to seek ways to strengthen at basic health care, especially FHS, leaving behind the history of asylums and unnecessary hospitalizations which haunt our country and the MPs.